Tributação, desigualdade excessiva e sustentabilidade pluridimensional - Figueiredo, Luís Carlos (2017)
The world undergoes serious social and environmental unbalances, whose perverse effects are felt in the most diversified areas of daily life. Such imbalances, despite existing for a long time, have reached alarming levels in the last years. This scenario, although murky, is still reversible, but it is necessary, however, to redefine the relationships of human beings with each other and with natural and anthropic environments. In this regard, it is needed to redefine the concept of sustainability established in the Brundlant report, replacing it with a multidimensional conception, better suited to the new times and challenges to be faced and that contemplates an economically efficient, balanced, environmentally clean and socially inclusive development, politically democratic and ethically committed to present and future generations. However, the construction of this multidimensional sustainability faces several obstacles, among which the excessive inequality stands out, for the market economy, despite being a powerful tool for generating wealth, has also ensured that these were accumulated in the hands of a few people. The excessive inequality, after a retreat in the thirty years that followed the World War II (at least in western European countries), has been increasing in the last forty years, even in the rich countries, mainly due to the implementation of economic policies that defend the minimum State, deregulation of the economy, reduction of the tax burden on patrimony and income and the proliferation of tax havens. Such inequality constitutes a serious threat to the environmental balance, economic efficiency, social cohesion and democracy. In this context, the tax exemption of wealth and income, associated with tax evasion, have made even more acute the tax regressity. In Brazil, excessive inequality has an intimate link with tax regressivity, which consists in a powerful barrier to the construction of multidimensional sustainability that, although it is a principle-binding and supreme value of the Brazilian legal system since the advent of the Federal Constitution of 1988, has not been effective until the present day. In our Democratic State of Law, taxation plays an important role not only as a source for public policies and the state machine, but also as an inductor of actions for the regulation of the market economy and the achievement of fundamental rights. However, paradoxically, shortly after the implementation of the Federal Constitution in 1988, there was a significant tax exemption to the withholders of capital, disregarding the principle of the contributory capacity and the fundamental duty to pay taxes. This perverse and iniquitous framework, however, can and must be urgently reversed, with the use of the existing tax and fiscal instruments in our legal order, which, without aggression to the Rule of Law, have the capacity to contribute significantly to eliminate excessive inequality and build the necessary multidimensional sustainability in Brazil.